2013
DOI: 10.1097/mnm.0b013e3283617d5b
|View full text |Cite
|
Sign up to set email alerts
|

The role of single-photon emission computed tomography/computed tomography in localizing parathyroid adenoma

Abstract: With hybrid imaging playing an increasingly important role in nuclear medicine, this article reviews the literature on single-photon emission computed tomography/computed tomography (SPECT/CT) in parathyroid scintigraphy. An understanding of parathyroid and neck anatomy is important for accurate reporting of these scans, as this can have an impact on the surgical approach used. The contribution of SPECT/CT over and above SPECT alone is greatest in terms of localization, particularly for ectopic tumours. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…It is important to accurately localize the abnormal parathyroid gland(s) in patients with PHPT referred for surgery . In this setting, 99m Tc‐MIBI SPECT and especially 99m Tc‐MIBI SPECT/CT may be the optimal choice . Several studies have assessed the accuracy of 99m Tc‐MIBI SPECT/CT for detecting hyperfunctioning parathyroid glands in patients with PHPT, but the results varied significantly .…”
Section: Discussionmentioning
confidence: 99%
“…It is important to accurately localize the abnormal parathyroid gland(s) in patients with PHPT referred for surgery . In this setting, 99m Tc‐MIBI SPECT and especially 99m Tc‐MIBI SPECT/CT may be the optimal choice . Several studies have assessed the accuracy of 99m Tc‐MIBI SPECT/CT for detecting hyperfunctioning parathyroid glands in patients with PHPT, but the results varied significantly .…”
Section: Discussionmentioning
confidence: 99%
“…In comparative studies, sensitivity, specificity, and accuracy have been found to be higher in SPECT/CT imaging compared with planar and SPECT imaging, especially in patients with previous neck surgery, ectopic adenoma, and multiglandular disease. Moreover, SPECT and especially SPECT/CT would be able to ascertain whether parathyroid adenoma is anteriorly or posteriorly based and this would guide the focused lateral or focused central incision approach [28][29][30]. In our study, we recorded anterior, posterior, and lateral planar scintigraphic images to obtain information on the location and depth of the parathyroid lesions and to determine the incision site.…”
Section: Discussionmentioning
confidence: 98%
“…The nuclear imaging has an important role in localizing the parathyroid glands. The association between cervical echography and 99m Tc- MIBI scintigraphy has a sensibility of 78–96% [9]. …”
Section: Discussionmentioning
confidence: 99%
“…The nuclear medicine imaging - especially the parathyroid scintigraphy with 99m Tc-MIBI (methoxy-isobutyl-isonitrile)- has an important role in outlining the diagnosis, being the chosen examination for the imaging representation of the parathyroid metabolism [911]. …”
Section: Introductionmentioning
confidence: 99%